Impact of Intravenous Tranexamic Acid on Hemorrhage During Endoscopic Sinus Surgery - Saidollah Nuhi; ali goljanian; Leyla Zarkhah; bahram rashedi (Iranian Journal of Otorhinolaryngology, 2015)
Introduction: Endoscopic sinus surgery is a common procedure performed by otolaryngologists. This study evaluated the efficacy of intravenous (IV) tranexamic acid (TA) on hemorrhage  in patients undergoing elective endoscopic sinus surgery (ESS).   Materials and Methods: The present study was performed in 170 patients scheduled for ESS surgery under general anesthesia in order to examine the effects of IV TA on providing a bloodless surgical field and to evaluate the amount of bleeding. One hundred patients received intravenous TA and 70 patients received placebo. Intraoperative hemorrhage was estimated by the attending anesthesiologist at the end of surgery by accounting for loss of blood and irrigation fluid in a 25 mL-graded suction canister and nasopharyngeal packing (measured weight of packing on the electronic scale). Hemodynamic variables were monitored and coagulation profile was determined.   Results: A total of 170 patients (90 male [53%] and 80 female [47%]), mean age 30.54±4.14 years, were evaluated. There was a significantly lower bleeding volume in the TA group than in the placebo group (107.7±45.1 vs. 189.3±51 mL; P0.05). Moreover, the difference between the TA and control groups regarding postoperative hematocrit (34.65±4.45 vs. 36.60±3.35) and hemoglobin (10.81±2.1vs. 11.64±1.9) levels was not significant (P>0.05). Vomiting and nausea in the control group was greater than in the control group, but the difference was not significant (P>0.05). We did not detect significant coagulation alterations in the TA group.   Conclusion:  TA significantly decreased hemorrhage without increasing side effects such as alteration in coagulation parameters, hemodynamic changes, and vomiting and nausea. Use of TA can avoid the need for antihypertensive agents to reduce blood loss in ESS.